UTUKKŪ LEMNŪTU (UDUG-HUL) IN A NEW TEXT FROM THE IRAQ MUSEUM. (December 2020) - Ali, Munther; Geller, Markham J.
Abstract : A small tablet fragment acquired by the Iraq Museum raises interesting questions, although at first it appeared to be a simple duplicate manuscript from the large bilingual incantation series Udug-hul. Publishing this fragment has drawn attention to an interesting feature of Mesopotamian incantations, in which the āšipu -exorcist protects himself first, before addressing the patient. Although this practice has been known from Tablet 3 of Udug-hul incantations, it turns out that Assur exorcists occasionally inserted their own names into otherwise anonymous incantations and prayers, in order to ensure their own protection, which is a practice not known from other sites.